Exploring ethical principles and values in the surgical care of the geriatric patient: a humanized and emergent approach - Díaz Pérez, Anderson; Castro Novoa, Albeis; Villegas Pacheco, Andrea Carolina; Yáñez Torregrosa, Zuleima; Cabarcas Teheran, Yoliseth; Roca Pérez, Angélica; Acuña Pérez, Wendy (Acta Bioethica, 2024)
The objective of this research is to describe the meanings and practices from the values and principles that emerge during the humanized care provided by the surgical team to the geriatric patient scheduled for surgery. Through the qualitative and interpretive paradigm, and from an objectivist and methodological epistemic framework, the perception existing among surgeons on how humanized care should be towards the elderly is reflected. Ten surgeons were interviewed through semi-structured sessions, and the analysis was carried out using the matrix of categories with the support of the ATLAS Ti 8.0 ® program. The perception of surgeons regarding humanized care considers that care is strengthened during the higher education they receive at the university and is fortified through the norms that govern the profession, in the sense of always aiming for the well-being and respect for the dignity of patients, especially the most vulnerable.